NOX4-Derived ROS Mediates TGF-β1-Induced Metabolic Reprogramming during Epithelial-Mesenchymal Transition through the PI3K/AKT/HIF-1α Pathway in Glioblastoma. (28th June 2021) - Su, Xiangsheng; Yang, Yihang; Guo, Changfa; Zhang, Rui; Sun, Shicheng; Wang, Yanjun; Qiao, Qiujiang; Fu, Yibing; Pang, Qi
Abstract : Current studies on tumor progression focus on the roles of cytokines in the tumor microenvironment (TME), and recent research shows that transforming growth factor- β 1 (TGF- β 1) released from TME plays a pivotal role in tumor development and malignant transformation. The alteration in cellular metabolism is a hallmark of cancer, which not only provides cancer cells with ATP for fuel cellular reactions, but also generates metabolic intermediates for the synthesis of essential cellular ingredients, to support cell proliferation, migration, and invasion. Interestingly, we found a distinct metabolic change during TGF- β 1-induced epithelial-mesenchymal transition (EMT) in glioblastoma cells. Indeed, TGF- β 1 participates in metabolic reprogramming, and the molecular basis is still not well understood. NADPH oxidases 4 (NOX4), a member of the Nox family, also plays a key role in the biological effects of glioblastoma. However, the relationship between NOX4, TGF- β 1, and cellular metabolic changes during EMT in glioblastoma remains obscure. Here, our findings demonstrated that TGF- β 1 upregulated NOX4 expression accompanied by reactive oxygen species (ROS) through Smad-dependent signaling and then induced hypoxia-inducible factor 1 α (HIF-1 α ) overexpression and nuclear accumulation resulting in metabolic reprogramming and promoting EMT. Besides, inhibition of glycolysis reversed EMT suggesting a causal relationship between TGF- β 1-induced metabolic changes and tumorigenesis. Moreover, TGF- β 1-induced metabolic reprogramming and EMT which modulated by NOX4/ROS were blocked when the phosphoinositide3-kinase (PI3K)/AKT/HIF-1 α signaling pathways were inhibited. In conclusion, these suggest that NOX4/ROS induction by TGF- β 1 can be one of the main mechanisms mediating the metabolic reprogramming during EMT of glioblastoma cells and provide promising strategies for cancer therapy.